2009
DOI: 10.1007/s10608-009-9247-9
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Its Relationships with Dissociative Experiences, Body Dissatisfaction and Eating Disturbances in a Non-Clinical Female Sample

Abstract: The purpose of the present study was to investigate, in a non-clinical sample of undergraduate women, the relationships between alexithymia, dissociative experiences and body dissatisfaction, while identifying the predictive factors associated with a potential risk of developing eating disorders (EDs). The Toronto alexithymia scale (TAS-20), dissociative experiences scale (DES), eating disorder inventory-2 (EDI-2), body shape questionnaire (BSQ), symptom checklist revised (SCL-90-R) and rosenberg self-esteem s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 62 publications
(60 reference statements)
11
21
0
1
Order By: Relevance
“…Alexithymia, shame, and affect dysregulation are strictly related as demonstrated by the correlations observed in our study; our data agree with the findings of De Berardis et al7 In their paper, the researchers noticed that dissociative experiences may be related to childhood neglect and abuse history;30 a history of abuse and neglect are observed more frequently in subjects with EDs, and in particular, among bulimic patients 31. Moreover, both childhood physical and sexual abuse appear to be associated with emotional dysregulation 32.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Alexithymia, shame, and affect dysregulation are strictly related as demonstrated by the correlations observed in our study; our data agree with the findings of De Berardis et al7 In their paper, the researchers noticed that dissociative experiences may be related to childhood neglect and abuse history;30 a history of abuse and neglect are observed more frequently in subjects with EDs, and in particular, among bulimic patients 31. Moreover, both childhood physical and sexual abuse appear to be associated with emotional dysregulation 32.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, a prognostic study by Speranza et al6 investigating 102 ED patients demonstrated that difficulty in identifying feelings can act as a negative prognostic factor in the long-term outcomes of EDs. De Berardis et al7 studied the relationship between alexithymia, dissociative experiences, and low self-esteem in 546 undergraduate females, stating that a combination of these three constructs may represent risk factors for developing the symptoms of EDs. However, the relationship between EDs and alexithymia is not completely understood; ED patients that are being treated may continue to score high on measures of alexithymia, even when food-related abnormal behaviors have remitted 8.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies have investigated links between emotional awareness and attitudes associated with body image disturbances (De Berardis et al, 2007; De Berardis et al, 2009; Manjrekar & Berenbaum, in press), though no studies have specifically examined relations between emotional awareness and PBB. Two studies (De Berardis et al, 2007; De Berardis et al, 2009) investigated relations between attitudes related to body image (i.e., body satisfaction) and alexithymia.…”
mentioning
confidence: 99%
“…Thus, when a memory is retrieved, emotions peripheral to the event may be activated, as well as those central to the experience. In addition, dissociation is related to both schizotypy (Watson, 2001) and alexithymia (De Berardis et al, 2009) and thus individuals high in dissociation may lack emotional clarity and they may be unable to distinguish between different emotions (e.g., (Berenbaum, Boden, & Baker, 2009). Finally, dissociation is also related to distractibility (Giesbrecht et al, 2008), which may lead to the re-experiencing of multiple emotions rather than a focus on the dominant emotions associated with the event in the memory.…”
Section: Discussionmentioning
confidence: 99%
“…To that end, participants were asked to retrieve and rate two achievement-related memories and a memory unconstrained by domain or valence. As reviewed above, we expected that participants high in dissociation would have memories saturated with negative affect and power motivation due to their negative self-views (De Berardis et al, 2009) and feelings of shame (DePrince et al, 2010; Talbot et al, 2004) and helplessness (Irwin, 1998b)…”
Section: Studymentioning
confidence: 99%